Transformasi Digital Pelaksanaan Pembelajaran Tematik di Sekolah pada Masa Pandemi - Vinca Desti Mardiana; Dian Hidayati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2022)
The COVID-19 pandemic has resulted in changes in the implementation of education from face-to-face learning to distance learning, thus demanding a digital transformation through the use of technology. The purpose of this study was to determine the form and process of digital transformation carried out in carrying out thematic learning activities during the distant learning period at the basic education level. The data collection technique used was interviews involving the principal, and two teachers as research resource persons. Data analysis includes collection, reduction, display, and verification/conclusion. The results showed that SD Al Azhar 38 Bantul carried out a digital transformation in thematic learning during the covid-19 pandemic by utilizing platforms such as pintro, zoom, google meet, and whatsapp. Meanwhile, the digital transformation process carried out by SD Al Azhar 38 Bantul itself went through several stages, namely digital transformation planning; organizing digital transformation; implementation of digital transformation; and control over digital transformation.